Anaesthesia for facial trauma. Issue 9 (September 2020) - Lewis, Grant; Niciu, Cristina; Fitzpatrick, Kevin
Abstract: Facial trauma is common and can produce both physical and psychological problems for patients. Managing patients in both the emergency setting and elective theatre environment can be extremely challenging, so airway interventions should be carefully planned so the safest and most effective technique can be chosen. This may mean that direct laryngoscopy may not be the safest or most straightforward option and awake tracheal intubation, videolaryngoscopy, submental intubation or awake tracheostomy may be a better choice in a given set of circumstances. An understanding of common mechanisms of injury and pathologies and the likely difficulties that will be present are essential. Senior anaesthetic input and effective teamwork is required to provide excellent levels of care for these patients.